Cost Control And Financial Performance Of Pharmaceutical Firms In Nigeria - Ajala, Oladayo Ayorinde (HM Journals, 2021)
This paper examined the impact of cost control on financial performance ofpharmaceutical firms in Nigeria from 2010 to 2019. Secondary data were used in thisstudy. The secondary sources of data were sought from published annual reports of the sixquoted pharmaceutical firms in Nigeria. The variables used in the study include; Profitafter Tax (PAT), Cost of Raw Material (CRM), Selling and Distribution Expenses (SDE),Salaries and Wages (SWE), Research and Development (RDC) and Training (TEC). Panelregression analysis was employed to evaluate the impacts of cost control on financialperformance of pharmaceuticals firms in Nigeria. The results revealed that cost controlhas significant influence on financial performance of pharmaceuticals firms in Nigeria.The study recommended that the management of the firms should adopt modern strategiccost management method for effective operation in the organization in order to enhancetheir performance.